The effect of pH and biomass concentration on cadmium (Cd) uptake by saccharomyces cerevisiae from simulated waste water - Mohd Hassan, Mohd Shuib (2006)
The contamination of wastewaters, river sediments and soil with toxic metals, is a complex problem. The removal of these contaminations has received much attention in recent years using conventional methods such as chemical reduction, ion exchange, and electrochemical treatment. The alternative method is discovered which is biosorption, refers to a physico-chemical binding of metal ions to biomass. Microorganisms like bacteria, yeast and fungi as well as algae can accumulate large amounts of heavy metal ions. Biosorption is considered to be a fast physical or chemical process. The biosorption rate depends on the type of the process. The biosorption of cadmium ions from artificial aqueous solutions using baker's yeast biomass is investigated. The major purpose of this research is to study the effect of pH and biomass concentration on cadmium uptake by Saccharomyces cerevisiae from simulated waste water. The effect of pH on biosorption was studied in the pH ranges of 3.0–8.0 for Cd2+ while effect of concentration on biosorption in the range of 5.0 – 17.5 mg/ml of the biomass. As a result, pH value of 3.0 shows a highest percent of metal accumulated and for the biomass concentration profile, the analysis for 15mg/ ml giving the maximum uptake of cadmium from the biosorbent.